PERAN BADAN PENGELOLAAN KEUANGAN, PENDAPATAN DAN ASET DALAM MENINGKATKAN PENERIMAAN PAJAK MINERAL BUKAN LOGAM DAN BATUAN - Muhammad Syoufi Lubis; M. Nazaruddin M. Nazaruddin; Rusydi Abubakar (Jurnal Transparansi Publik (JTP), 2021)
This research examines the role Financial Management Agency, Revenue in Increasing Non-Metal Mineral and Rock Tax Revenue, it is known that in 2016-2020 there was a significant decrease in the realization of tax revenues (in 2016 the realization was Rp. 1.887.075.092,- until 2020 the realization only reached  Rp. 305.450.406,-). This decrease was due to a change in the collection system used in collecting taxes on non-metallic minerals and rocks in 2016-2020 from an official assessment system to a self assessment system. The theory used to analyze the problem is the implementation theory according to Edwards III with four main indicators including communication, resources, disposition, and bureaucratic structure. The research method use a gualitative approach. Date collection techniques through observation, interviews and documentation. The results showed that tax revenues for non-metallic minerals and rocks continued to decline in Bener Meriah Regency from 2016-2020, using the self assessment system as a system for collecting taxes on non-metallic minerals and rocks that were still not effectively implemented. What steps are taken to increase tax revenues for non-metallic minerals and rocks in Bener Meriah Regency are due to the lack of socialization of the regulations that have been set and coordination of information delivery among tiered officials. Resources that are lacking in carrying out supervision in the form of tax collectors for non-metallic minerals and rocks.Weak disposition with lack of seriousness in tax collection management. The bureaucratic structure with a lack of coordination is the cause of the lack of information and communication carried out by officials who collect taxes on non-metallic minerals and rocks at BPKPA, Bener Meriah Regency